Penerapan Perpaduan Metode Kooperatif Model Student Teams Achievment Division Dan Talking Stick Untuk Meningkatkan Hasil Belajar Siswa Kelas X MIA 3 SMAN 1 Lawang - Ria Ratih Puspasari; Prih Hardinto (Universitas Negeri Malang, 2016)
This study aims to: (1) to determine the implementation of cooperative learning model of STAD (Student Teams Achievement Division) and Talking Stick on the subjects of Economics students of class X MIA 3 SMAN 1 Lawang, (2) to determine whether the application of cooperative learning model of STAD (Student Teams Achievement Division) and Talking Stick can improve student learning outcomes class X MIA 3 SMAN 1 Lawang.This research is a classroom action research with qualitative descriptive approach. This study consisted of two cycles, each cycle consisting of four phases, namely planning, implementation, observation and reflection. research subjects are students of class X MIA 3 SMAN 1 Lawang academic year 2015/2016 totaling 35 students. Methods of data collection in this study using observation, test questions, interviews, field notes, and documentation.The results of this study showed an increase in student learning outcomes affective and cognitive aspects. To increase students' cognitive aspects, can be seen from the pre-test and post-test cycle I and cycle II. At the time of the pre-test the first cycle, the number of students who completed as many as 2 (5.71%), whereas in post-test complete student number increased to 28 people (80%). At the time of the pre-test cycle II, the number of students who completed as many as five people (14.2%), whereas in post-test complete student number increased to 32 (91.4%). Overall, the average results of post-test cycle I and II increased by 6.5%. Besides being able to improve student learning outcomes affective and cognitive aspects. Keywords: STAD, Talking Stick, Learning Outcomes